Analysis of the Performance of SMEs Credit Program in the Stakeholders' Perspectives - Nasir, Mohamad (Badan kebijakan Fiskal, 2013)
SMEs have siginifcant role for Indonesian economic, such as employing many labors and significant contribution to GDP. To support them more productive, Government launched a KUR in 2007, a credit program for SMEs that is feasible but not bankable, and has credit guarantee facility. Government has cooporated with some Banks for credit and with PT Askrindo and Perum Jamkrindo for credit guarantee. Since 2007, KUR has been run over 5 years. The question is how the performance of KUR viewed by Government, Banks, and Credit Guarantee Enterprises perspectives. Bu using descriptive analysis methode, the research shows that for Government perspective, KUR has distributed credit around Rp.97.6 triliun for around 7.6 million debitors during 2007-2013. For perspective of Banks, KUR has given profit because its interest rate (13% for retail and 22% for mikro] above basic lending rate of banks. Credit guarantee facility also has supported banks to penetrate new market or new debiturs. For credit guarantee enterprises, KUR has been able to increase their income.